What explains student's intentions to pursue a certified professional accountancy qualification?. Issue 2 (14th June 2018) - Owusu, Godfred Matthew Yaw; Obeng, Victoria Asantewaa; Ofori, Charles Gyamfi; Ossei Kwakye, Teddy; Bekoe, Rita Amoah
Abstract : Purpose: This study examines the factors that explain Ghanaian business students' intentions to pursue a Certified Professional Accounting (CPA) qualification. Design/methodology/approach: The study uses survey method of research and mainly used questionnaires as data collection instrument to elicit information from the respondent group. Using a total of 641 business students from the University of Ghana Business School, a mixture of factor analysis and logistic regression analysis techniques was used in investigating the study objectives. Findings: Results from the regression analysis demonstrate that students' preference and beliefs about accounting professional qualification, academic major and grade point average are significantly associated with their intentions to pursue a CPA qualification. Moreover, majority of the sampled respondents (47.9 per cent) with the desire to pursue a CPA qualification prefer to be affiliated with the Association of Chartered Certified Accountants, 27.2 per cent prefer the Institute of Charted Accountant Ghana qualification, while only 7 per cent of the students prefer to be affiliated with the Chartered Institute of Management Accountant. Research limitations/implications: The findings from this study have important implications for the various professional accountancy bodies, accounting educators and other stakeholders interested in promoting the choice of accounting as a career path among university students. Practical implications: The results indicate that, as part of the broader strategy to increase the number of professional accountants in Ghana, there is the need to promote the study of accounting at the undergraduate level in the various universities in the country. Originality/value: This study uniquely uses the behavioral decision theory to explain the dominant factors associated with students' intentions to pursue a CPA qualification.